Behavior of Violence in Education: Study of Education Sociology - Ansori Ansori; Antonia Junianty Laratmase; Syahrir Ibnu (ijd-demos, 2022)
AbstractMoral education is essential in the world of education. Moral education does not teach about academics but non-academics, especially about attitudes and how to do good daily behavior. Moral education has been defeated by other education. Time at school is used up to pursue academic values. Students are forced to study so that their grades on exams will improve and they can live up to the name where they attend school. The teacher forgets that a lesson is more important than all of that, namely moral education. This relationship pattern is rooted in the non-objectivity of the education system in Indonesia, namely regarding the principles, objectives, social organization, curriculum, teaching methods, evaluation, students, educators, facilities, and financing. Value education is a learning effort for students to understand and recognize, instill and preserve, absorb and realize noble values in human life related to truth, goodness, and beauty in habituation to act consistently with value demands. In society, many roles of parents are left in educating their children to other people or household assistants. Of course, these children have a character or character that will be much different from the nature of their parents. The child will tend to follow what he sees, which is fun, without being aware of the good, bad, right, wrong, reasonable, unreasonable, inappropriate, may not all of these be rammed. His family and life should not be ignored and neglected. Even though the current trend is due to the increasing material needs, many mothers and fathers work and surrender their children’s life problems to household assistants or “paid people” so that almost all educational matters are entirely relied on by schools and, unfortunately, in schools, intellectual issues, moral values are practically untouched.Keywords: Behavior of Violence, Education Sociology, Students AbstrakPendidikan akhlak merupakan hal yang esensial dalam dunia pendidikan. Pendidikan moral tidak mengajarkan tentang akademik tetapi nonakademik, terutama tentang sikap dan bagaimana berperilaku sehari-hari yang baik. Pendidikan moral telah dikalahkan oleh pendidikan lain. Waktu di sekolah habis untuk mengejar nilai-nilai akademik. Siswa dipaksa untuk belajar agar nilai ujian mereka meningkat dan mereka dapat mengharumkan nama sekolah tempat mereka bersekolah. Guru lupa bahwa suatu pelajaran lebih penting dari itu semua, yaitu pendidikan akhlak. Pola hubungan ini berakar pada non-objektivitas sistem pendidikan di Indonesia, yaitu mengenai asas, tujuan, organisasi sosial, kurikulum, metode pengajaran, evaluasi, peserta didik, pendidik, fasilitas, dan pembiayaan. Pendidikan nilai merupakan upaya pembelajaran bagi peserta didik untuk memahami dan mengenal, menanamkan dan melestarikan, menyerap dan mewujudkan nilai-nilai luhur dalam kehidupan manusia yang berkaitan dengan kebenaran, kebaikan, dan keindahan dalam pembiasaan bertindak sesuai dengan tuntutan nilai. Dalam masyarakat, banyak peran orang tua yang ditinggalkan dalam mendidik anaknya kepada orang lain atau asisten rumah tangga. Tentunya anak-anak tersebut memiliki watak atau watak yang akan jauh berbeda dengan sifat orang tuanya. Anak akan cenderung mengikuti apa yang dilihatnya, yang menyenangkan, tanpa menyadari baik, buruk, benar, salah, wajar, tidak masuk akal, tidak pantas, tidak boleh semua itu ditabrak. Keluarga dan hidupnya tidak boleh diabaikan dan diabaikan. Meski tren saat ini karena kebutuhan materi yang semakin meningkat, banyak ibu dan ayah yang bekerja dan menyerahkan masalah kehidupan anak-anak mereka kepada asisten rumah tangga atau “orang bayaran” sehingga hampir semua urusan pendidikan sepenuhnya diandalkan oleh sekolah dan, sayangnya, di sekolah, masalah intelektual, nilai moral praktis tidak tersentuh.Kata kunci: Perilaku Kekerasan, Sosiologi Pendidikan, Siswa